Decidual expression and localization of human surfactant protein SP-A and SP-D, and complement protein C1q. Issue 2 (August 2015) - Madhukaran, Shanmuga Priyaa; Kishore, Uday; Jamil, Kaiser; Choolani, Mahesh; Lu, Jinhua
Abstract: Surfactant proteins SP-A and SP-D, and complement protein C1q are soluble innate immune pattern recognizing molecules. SP-A, SP-D and C1q have an overall similar structure composed of an N-terminal triple-helical collagen region that is followed by a trimeric globular domain. While SP-A and SP-D belong to the collectin family (collagen containing lectin), C1q is the first recognition subcomponent of the classical pathway of the complement system. Recently, SP-A, SP-D and C1q have been considered to play important roles in early and late pregnancy. However, their expression in early human decidua has not been examined. Here, we investigated whether SP-A, SP-D and C1q are expressed within first trimester decidua in humans and their expression is associated with trophoblasts and decidual stromal cells. Decidual samples from women undergoing elective vaginal termination of pregnancy during first trimester were obtained from 25 subjects. Immunohistochemical studies using anti-human SP-A, anti-human SP-D and anti-human C1q antibodies were performed on decidual tissue sections along with anti-vimentin and cytokeratin-7 antibodies to identify stromal cells and trophoblasts. The expression was also examined by immunostaining and PCR using decidual and stromal cells. C1q expression was significantly higher when compared to SP-A and SP-D in the first trimester human decidua. Double immunostaining revealed that all stromal cells and trophoblasts expressed SP-A, SP-D and C1q, while only few invasive trophoblasts expressed C1q. Thus, expression of SP-A, SP-D and C1q in human decidua during first trimester suggests potential role of SP-A, SP-D and C1q during the early stages of pregnancy including implantation, trophoblast invasion and placental development.